Avaliação da aplicação das boas práticas de laboratório e sistemas da qualidade, em instituições públicas de pesquisa e ensino superior na área de saúde no Brasil - Camurça, Ernestina Maria Nunes (2006)
To make possible the implantation of management techniques and good practice of laboratory on the Brazilian Net of Laboratories - REBLAS from an evaluation of diagnosis, for the application of questionnaires in laboratories of public institutions of superior education and health research, in four Brazilian capitals. Methodology: The research was carried through visits in laboratories of institutions of superior education and health research, to diagnosis the situation of them by interviews with application of questionnaires. The size of the sample was in fifty (50) researchers, distributed in institutions of education and research of four (04) Brazilian capitals. In each institution had been selected a laboratories and identified the responsible researchers to be interviewed. After that, a diagnosis of the situation of the laboratories was elaborated, and been compared with previously existing models of good practice of laboratory in literature, which had been evaluated and lead under absolute secrecy, in order to keep the integrity of the laboratories and institutions in question. Results: through the diagnosis of the laboratories were developed models of good practice of laboratory and quality warranty (operational procedures standard and forms), which could be implanted and be implemented in laboratories of institutions of existing health education and research in Brazil. Conclusion: The theoretical conceptions that had based the study had been analyzed and compared with the theoretical research and on field and had made possible the choice and elaboration of management techniques and standardized procedures in function of the diagnosis of the interviewed laboratories. This will be able to reflect trust in the scientific community through the implantation of procedures and standardized techniques and in the future those laboratories may be credential in the REBLAS, conferring security to the researchers, as well as, credibility of the results.